2011
DOI: 10.1186/1471-2296-12-37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online palliative care training on knowledge, attitude and satisfaction of primary care physicians

Abstract: BackgroundThe Spanish Palliative Care Strategy recommends an intermediate level of training for primary care physicians in order to provide them with knowledge and skills. Most of the training involves face-to-face courses but increasing pressures on physicians have resulted in fewer opportunities for provision of and attendance to this type of training. The effectiveness of on-line continuing medical education in terms of its impact on clinical practice has been scarcely studied. Its effect in relation to pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 29 publications
3
104
0
2
Order By: Relevance
“…This finding mirrors that of Pelayo et al, (2011) who, through a randomised controlled trial with 169 primary care physicians, found those undertaking the online learning package showed a significant increase in knowledge, perceived confidence in symptom management and communication, when compared to the half of the group receiving traditional teaching methods. In addition, the benefits of developing knowledge on how to manage sensitive issues in an online learning situation were noted.…”
Section: Discussionsupporting
confidence: 61%
“…This finding mirrors that of Pelayo et al, (2011) who, through a randomised controlled trial with 169 primary care physicians, found those undertaking the online learning package showed a significant increase in knowledge, perceived confidence in symptom management and communication, when compared to the half of the group receiving traditional teaching methods. In addition, the benefits of developing knowledge on how to manage sensitive issues in an online learning situation were noted.…”
Section: Discussionsupporting
confidence: 61%
“…Prominent differences in ratings between methods (i.e., .30% difference in positive rating between at least 2 of the methods) were noted by at least 1 subgroup in 8 of the survey questions (4,(7)(8)(9)(10)(11)(12)(13). While this did not trend in favor of any one method, participants ultimately indicated that they were most willing to use the PowerPoint method.…”
Section: Discussionmentioning
confidence: 90%
“…5 Recent advances in Web technologies and applications have led to an increase in the popularity of distance learning programs in health care education. Technical, logistical, and cost-related limitations still exist (particularly in international collaborations), 11,13,14 but even so, the specialty of radiology, because it is largely image based, seems well positioned to transfer a portion of its course delivery to an online format.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations